The use of word construction models in terminology teaching - Velička, A.; Križinauskas, J. (Psichologija, 1973)
The article analyzes the questions of terminology teaching in nonhumanitarian high school. One of the major questions is the selection of lexical, grammatical and word composition minimum. It is most difficult to understand the text without knowing the terminology, because word composition constitutes partially open systems and thus the discrepancy between the system and the norm becomes noticeable. In specialty texts the noun is the most common speech part from the structural approach and thus it is important to determine and select its composition methods. The research conducted at Vilnius Institute of Engineering constructions showed that the knowledge of word composition models enables the disclosure of a considerable part of meaning in terminology – compound nouns (22,2%), derivative words (12%) and conversions (25%). Thus the productive models of word composition, which are very helpful in using the analogy, should receive a proper consideration.
Keywords: word construction; teaching of terminology